Review Artikel : Persebaran Famili Anisakidae yang Menginfeksi Ikan Laut di Indonesia - Putri Desi Wulan Sari; Sri Subekti; Yarin Dwi Monica (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: Family of Anisakidae is one of the zoonotic helminth parasitics. The distribution of the family Anisakidae is extensive. It needs to be known because the diversity of parasites can provide information about the distribution area and impact of the parasites of the family Anisakidae in Indonesia. This review article summarises the distribution of parasites from the family Anisakidae that infects marine fish and the factors that influence Indonesia. Methods: This research is qualitative research through literature study as the main object. The data from the literature study results are presented in tables and figures then explained descriptively. Results: The distribution of Anisakidae in Indonesia is found in four genera, namely the genus Anisakis, Pseudoterranova, Terranova and Contracaecum, which are mostly found from the carnivorous marine fish of the family Balistidae, Carangidae, Epinephelidae, Lutjanidae, Priacanthidae, and Scombridae Conclusions: Four genera of endoparasitic worms from the Anisakidae family were reported to infect Indonesian marine fish, including Anisakis, Pseudoterranova, Terranova and Contracaecum. Temperature, salinity, hosts' presence, and anthropogenic factors are biotic and abiotic factors that can affect the distribution of Anisakidae. The information on this literature study results is hoped to be used as the basis for developing research in fish parasitology in particular and increasing public awareness of fish processing in general.